Perancangan Sistem Informasi Inventory Berbasis Web dengan Menggunakan Metode Spiral - Arya Nibras Nayottama Sidiki; Abdul Goni; Achmad Rizqullah Blessar; Auliya Putri Amanda; Muhammad Rival Aziz; Muhammad Vico Airlangga; Eva Zuraidah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
MSME Mamaku needs an inventory system that helps make work easier so that it doesn't take up too much time. For this reason, the author created an inventory system at MSME Mamaku which until now has not been computerized. Currently, MSME Mamaku is only a business that operates in the clothing production sector. The existing system at MSME Mamaku is still done manually, starting from recording incoming goods, recording outgoing goods, storing other data related to the inventory process, and making reports, so it is possible for errors in recording, less accurate reports being made, and requiring inefficient time, and delays in searching for the required data. The design of this inventory information system is the best solution to solve problems in these MSMEs, and with this computerized system, an effective and efficient activity can be achieved in carrying out activities in these MSMEs. The computerized system is better than the manual system because the proposed system is more effective and efficient and the current inventory system is more conducive compared to the previous system. The application is designed using the Spiral method, PHP programming language, Laravel framework, and MySQL as database storage. The result of designing an inventory system is a website that can record incoming and outgoing goods and print computerized reports.